PS-C19-3: HYDROCHLOROTHIAZIDE WAS NOT ASSOCIATED WITH PHOTOSENSITIVE OR PHOTOTOXIC REACTIONS AND DNA-DAMAGE IN VIVO AND IN VITRO (THE HCTOX-STUDY). (January 2023) - Goetzinger, Felix; Hohl, Mathias; Millenaar, Dominic Norman; Lauder, Lucas Douglass; Reichrath, Joerg; Meyer, Markus Robert; Boehm, Michael; Ukena, Christian; Mahfoud, Felix
Abstract : Objective: Pharmacoepidemiologic studies associated the use of HCT with an increased risk of skin cancer, resulting in a decrease of HCT prescriptions, in turn leading to worsening of blood pressure therapy in a significant proportion of patients. However, whether HCT causes skin cancer remains elusive. Hence, we aimed to examine the photosensitive and phototoxic potential of HCT in vivo in a randomized, placebo-controlled trial. To further enlighten the pathophysiologic mechanisms of carcinogenesis and phototoxicity caused by HCT in vitro, we conducted a series of laboratory experiments. Design and method: A randomized, double-blind, placebo-controlled clinical trial to assess the phototoxic properties of HCT was conducted, assigning 30 healthy normotensive adult volunteers in a 2:1 ratio to either HCT 25 mg daily or placebo once daily for 15 days. The skin photosensitivity by phototesting, office blood pressure, serum 25-hydroxyvitamin D (25(OH)D) status and urinary excretion of thymidine-dimers, i.e. cyclobutan-dimers by ultra-high-performance liquid chromatography-high resolution mass spectrometry (UHPLC-HRMS) following whole-body irradiation were assessed. To further assess the pathophysiologic mechanisms of possibly HCT induced photosensitivity, human keratinocytes (HaCaT) were incubated with HCT and then irradiated with UV-B radiation (311 nm one burst of 100 J/cm2). rt-PCR-testing and western blots were performed to analyze reactive oxygen species, inflammation, and carcinogenesis. Results: All 30 participants were adherent to the protocol, which was confirmed by UHPLC-HRMS analysis of serum and plasma. Skin photosensitivity to exposure of UV-A and UV-B radiation did not change in both groups (HCT vs. placebo: MED-UVB change 0.0 J/cm2 vs. 0.2 J/cm2; p = 0.06). No thymidine-dimers were detectable in either group. Systolic blood pressure decreased in both groups (-5.2 mmHg vs. 5.4 mmHg; p = 0.94), as did diastolic blood pressure (-4.3 mmHg vs. -1.9 mmHg; p = 0.34). Serum 25(OH)D increased in both groups (3.1 ng/ml vs. 1.2 ng/ml; p = 0.52). HCT in combination with a single high-intensity bursts of UV-B radiation was not associated with increased expression of inflammatory proteins, chronic inflammation and reactive oxygen species. Conclusions: HCT was not associated with increased photosensitivity for UV-A or UV-B radiation in healthy volunteers. Moreover, no relevant DNA-damages as measured by UHPLC-HRMS were detectable in either group. The combination of HCT treatment and a single burst of UV-B did not increase inflammatory markers. HCT appeared to be safe in healthy volunteers and was not associated with photosensitivity or DNA-damages in vivo.